Shared auditors, information asymmetry degree, and mergers and acquisitions value creation - You, Chunhui (Frontiers in Psychology, 2022)
Social network is an important factor that affects the value creation of mergers and acquisitions (M & A). The M & A events of China's Listed Companies in 2011-2018 were used as research samples, and this study used the ordinary least square method to test the value creation effect of shared auditors. First, it analyzed the impact of shared auditors on the current, short-term and long-term M & A value creation. Second, it analyzed the moderating effect of information asymmetry degree. The research results show that shared auditors can increase the enterprise value of both sides of M & A. In addition, related M & A and industry attributes can moderate the relationship between shared auditors and M & A value creation. When the M & A are unrelated and in different industries, shared auditors play a more significant role in the value creation of M & A that have more asymmetric information.